Comparison of the Training Skills of the Handball Trainers for the First and Second Classes in Iraq - Ahmed Kadhim Abdulkareem (Journal of Global Pharma Technology, 2019)
The research consisted of two axes: the level of communication skills and their comparison among the handball trainers for the category of applicants in Iraq. The training communication skills standard was developed and the descriptive method was used in a comparative manner to suit the nature of the research. The research sample included (20) trainers, and the comparisons between training skills were obtained using statistical means.Keywords: Training skills and handball trainers.